Fluorogenic RNA Mango aptamers for imaging small non-coding RNAs in mammalian cells - Alexis Autour; Sunny C. Y. Jeng; Adam D. Cawte; Amir Abdolahzadeh; Angela Galli; Shanker S. S. Panchapakesan; David Rueda; Michael Ryckelynck; Peter J. Unrau (Nature Communications, 2018)
Many aptamer-fluorophore complexes suffer from low quantum yield and low extinction coefficients limiting their usability. Here the authors isolate new Mango aptamers with improved fluorescent properties for both fixed and live-cell imaging by using competitive ligand binding microfluidic selection.